ENVIRONMENTAL ASSESSMENT OF THE AREIA BRANCA ECOTOURIST PARK (TRÊS FRONTEIRAS, SÃO PAULO): SUBSIDIES FOR LOCAL ENVIRONMENTAL CONSERVATION - Antonio Luiz, Gilberto; José Corbi, Juliano (Journal of Interdisciplinary Debates, 2024)
Parks are considered important for promoting sustainable development in cities and for offering ecosystem services. The environmental quality in the Parks and their anthropic occupation is a topic that must compose the public administration’s agenda. The present dissertation analyzed the occupation of the Ecotouristic Park of Areia Branca (Três Fronteiras, State of São Paulo) and its environmental risks, making a historical-legal and environmental survey of the area, in addition to subsidiarily helping in the formulation of public policies for the place. The Areia Branca Ecotouristic Park is of fundamental importance for the preservation of ecosystem services in the region, as in addition to serving as a cradle and development of animals and plants, they also protect the soil from erosion by rainwater in the headwaters, in addition to contributing to with aquifer recharge. The Park area consists of a green belt of medium and large vegetation, extending beyond the park over an extensive area. In this way, it protects rivers and streams from the action of pesticides from crops present in the area, in addition to being used for leisure, sports and to contain fishing areas. This research aims to analyze the services of the ecosystems present in the Park and raise risk situations for the environmental quality of its surroundings. The diagnosis of the area was carried out through a survey of ecosystem services (provision, regulators, support and cultural services) in the study area and its surroundings, through direct observations of the location, verifying possible agents causing changes. The environmental assessments of the indicated ecosystem services will serve to support public managers and environmental agents so that they can adopt protective measures aiming at a local environmental conservation policy, with a view to the sustainable development of the area. In the Park area, the presence of regulatory, support, provision and cultural services was verified, whose classification was proposed by the “Millennium Ecosystem Assessment”, based on the functionality of ecosystem services. The results obtained point to the existence of several services in the Park that contribute directly and indirectly to human well-being with relevant benefits for society, in terms of maintenance, recovery or improvement of local and regional environmental conditions.